Roles of isometric contraction training in promoting neuroprotection and angiogenesis after stroke in adult rats - Mei, C; Ma, T (Physiological research, 2022)
100 rats were randomly divided into a sham-operated group and middle cerebral artery occlusion (MCAO) modeling groups. The sham group after surgery was observed for 14 days. After MCAO, some rats received isometric contraction training (ICT) which was as follows: an atraumatic tourniquet was placed around left or right hind limb to achieve hind limb ischemia for 5 min, followed by 5 min of reperfusion, 4 cycles for one time, once a day, and five days per week. The MCAO modeling groups included the following four groups: i) a group only received MCAO, and was observed for seven days (MCAO-7d), ii) a group only received MCAO, and was observed for 14 days (MCAO-14d), iii) a group, after MCAO, received ICT for seven days (ICT-7d), and iv) a group, after MCAO, received ICT for 14 days (ICT-14d). Brain infarct area, behavioral outcomes, the number of neurons, apoptosis, cerebral edema and cerebral water content were assessed, respectively. The mRNA expression of vascular endothelial growth factor (VEGF) was assayed with RT-PCR, and protein expression of VEGF was quantified with western blot. compared with MCAO controls, cerebral infarction, neurological deficits and neuronal apoptosis were reduced significantly in the ICT groups, while the number of neurons was increased. Moreover, the mRNA expression of VEGF and protein expression of VEGF were enhanced after 1 and 2 weeks of ICT. ICT may promote angiogenesis and neuroprotection after ischemic stroke and this new remodeling method provide a novel strategy for rehabilitation of stroke patients.
Keywords: Vascular Endothelial Growth Factor A; ischemie mozku; Brain Ischemia; messenger RNA; Stroke; neuroprotekce; Isometric Contraction; kondiční příprava zvířat; krysa rodu Rattus; zvířata; cévní mozková příhoda; RNA, Messenger; potkani Sprague-Dawley; vaskulární endoteliální růstový faktor A; Neuroprotection; infarkt arteria cerebri media; Physical Conditioning, Animal; Infarction, Middle Cerebral Artery; Rats; Rats, Sprague-Dawley; isometrická kontrakce; Animals; Disease Models, Animal; modely nemocí na zvířatech